The quality of life and human development index of community living along Pahang and Muar river: a case of communities in Pekan, Bahau and Muar - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Ramli, Siti Aisyah (Canadian Center of Science and Education, 2012)
Rivers have something to do with the improvement of the quality of life of the rural community. A lot of benefits can be offered to the river community. This study intends to reveal the level of quality of life of the rural community living along two major rivers in Malaysia, the Pahang and Muar Rivers. Apart from this, this study intends to investigate the level of Human Development Index of the Pahang and Muar River community by using an established human development index known as the Well-o-Meter. This is a quantitative study, where a total of 900 respondents had been selected. A developed questionnaire was used and survey was employed. Based on the results gained, it can be identified that the respondents studied recorded a high level of mean score in the aspects of social involvement and relationship, home condition, safety at the areas and education. The human development index employed have detected that the respondents studied do have a low level of HDI. The findings of the study were further discussed.